Analisis Perubahan Struktural dan Pengaruhnya terhadap Ketimpangan Distribusi Pendapatan di Jawa Barat Tahun 2011-2019 - Herika Sofita Putri; Anugerah Karta Monika (Politeknik Statistika STIS, 2022)
All parties hope that the economic development process, which include establishing a good economy and implementing structural changes, will be able to increase income distribution equity. The purpose of this research is to describe the structural changes and income distribution inequality that occurred in West Java in 2011-2019, as well as to investigate the impact of structural changes on income distribution inequality. The analytical method was a panel data regression model with the random effect model as the chosen model. The analysis found that structural changes in West Java are unbalanced transformation, and that structural changes in production and labor have a statistically significant impact on income distribution inequality. With the characteristics, economic growth in the industrial sector has negative impact on income distribution inequality, economic growth in the service sector has a positive impact, and agricultural labor absorption has negative impact.